Lexical-Semantic Explication of Concept DEATH in Yakut language - N. N. Vasilyeva; A. M. Nikolayeva (Научный диалог, 2017)
Еhe results of the lexical-semantic explication of a universal concept of DEATH in the Yakut language picture of the world are presented. The relevance of the work is determined by the fact that the study of concepts, occupying a significant place in the Yakut linguistic culture, is not currently completed. It is also noted that linguists have always shown interest in the content of the concept of DEATH and peculiarities of its lexical representation by means of different languages, because it belongs to the universal concepts. Euphemization in of death designation is emphasized. The material of the research were sustainable verbal complexes of the Yakut language, signifying death. Prepared by the authors the literal translations of collocations are presented. For example, the expressions are given which literally can be translated as follows: “to disappear from white sun world,” “to go into the pit,” “to go out on the hillside,” “soul became cold” etc. The analysis involve phraseology with other meanings: ‘to deprive of life, kill,’ ‘to go on a deadly risk’ etc. They confirm and clarify the metaphors identified in the primary material. Vocabulary is analysed with respect to ethnographic background information about the traditions of the Yakut graves, about the attitude to suicide and others. Following models of ideas about death are revealed on the Yakut material: “death is a transmigration to another world,” “death is the end,” “death is darkness,” “death is sleep” etc.